Introducción al Sistema de Posicionamiento Global - Carrera Hurtado, Galo (My University, 2001)
The underlying aim regulatory international organizations in the implementation of ECDIS standars is to enable this technology to become functionally equivalent to the conventional paper chart for carriage purposes under the Safety of Life at Sea (SOLAS) convention.
Keywords: navigation; methods; ECDIS; obstacles; developments